Halal Regulation: Halal Self-Declare in Halal Certification - Maria Ulfa (Journal of Islamic Business Law, 2022)
Article 4A Halal Product Assurance Cluster Law No. 11 of 2020 on Job Creation states "For micro and small enterprise the obligation to be certified halal is based on statements by micro and small enterprise" this regulation aims to provide ease of doing business, especially in halal certification for micro and small enterpraises. The study of the existance of this regulation is needed by many perspectives. Two of them are by halal product assurance and maslahah mursalah. This paper uses a normative legal research method and aims to examine the harmony between Article 4 of Law no. 33 of 2014 on Halal Product Assurance and Article 4A of Halal Product Assurance Cluster Law no. 11 of 2020 on Job Creation and how to review the maslahah mursalah regarding halal self-declaring in the halal certification process. Based on the results of the study, it can be seen that, first, there is a harmonization between Article 4 of Law no. 33 of 2014 and Article 4A of the Halal Product Assurance Cluster Law no. 11 of 2020 on Job Creation. Conformity between the concept of maslahah mursalah and halal self declare. To create a climate of ease of doing business and assuranceing consumer rights, the synergy is needed between the government, businessman, and consumers.